EFEKTIVITAS PELAKSANAAN KOORDINASI DAN PEMBAGIAN TUGAS DALAM PROSES IMPLEMENTASI KEBIJAKAN PENERTIBAN PENGEMIS DI KOTA PONTIANAK - Eka Novie Diastuti E.01109093 (FISIP Universitas Tanjungpura, 2014)
Beggars controlling particularly in Pontianak City is very essential to be implemented since there are a number of beggars who wander in public places. These beggars’ activities indicate a violation of Local Rule of Pontianak City Number 1 of 2010 as regards of public order Article 41 verse 1b. Basically, beggars controlling have been carried out nevertheless in reality it often creates a discrepancy between coordination and division of labor that has been agreed upon. The purpose of this study is to investigate the effectiveness of coordination and distribution of duties in the process of beggars controlling policy implementation by employing descriptive qualitative analysis approach. The findings indicate that the coordination and distribution of duties carried out by the Department of Social Welfare and Labor of Pontianak City as well as Pontianak Civil Service Police Unit is still ineffectual. The implementation of beggars controlling with Standard of Operating Procedures (SOPs) should be performed appropriately and coordination among agencies involved in the implementation of beggars controlling in the city of Pontianak also need to be intensified. Hopefully this research will be beneficial for beggars controlling in Pontianak city. Keywords: coordination, distribution of duties, effectiveness